On the cost of opportunistic behavior in the public sector: A General-Equilibrium approach - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the wasteful effect of bureaucracy on the economy by addressing the link between opportunistic behavior of government bureaucrats and the public sector wage bill. In particular, public officials are modeled as individuals competing for a larger share of those public funds. A simple extraction technology in the gov- ernment administration is introduced in a standard Real-Business-Cycle (RBC) setup augmented with detailed public sector. The model is calibrated to German data for the period 1970-2007. The main findings are: (i) the model performs well vis-a-vis the data; (ii) Due to the existence of a significant public sector wage premium and the high public sector employment, a substantial amount of working time is spent in opportunistic activities, which in turn leads to significant losses in terms of output; (iii) The model-based loss measures obtained for the EU-12 countries are highly-correlated to indices of bureaucratic inefficiency.
Keywords: E69; E62; E32; J45; 330; rent-seeking; opportunism; bureaucracy; government emloyment and wages